Semisupine Positioning for Proximal Humerus ORIF Using Arthroscopic Shoulder Distractor. Issue 4 (April 2020) - Hightower, Cody; Mobley, Kyle; Jones, Thomas
Abstract : Summary: Advances in implant technology have improved the orthopaedic surgeon's ability to successfully treat proximal humerus fractures. However, obtaining and maintaining anatomic reduction throughout surgery remains difficult. Failure to do so can compromise surgical outcomes leading to poor clinical results. Here, we describe a novel surgical method using upper-extremity traction that allows control and positioning of the operative extremity. This technique facilitates achieving and maintaining fracture reduction and decreases operative time.